2022
DOI: 10.1007/s11042-022-13073-x
|View full text |Cite|
|
Sign up to set email alerts
|

Threshold image segmentation based on improved sparrow search algorithm

Abstract: Threshold segmentation based on swarm intelligence optimization algorithm is a research hotspot in image processing, because of its good segmentation effect and easy implementation. This paper proposes an image threshold segmentation method based on an improved sparrow search algorithm and 2-D maximum entropy method. In the proposed algorithm, the nonlinear inertia weight is introduced into the entrants’ update formula to improve the local exploration ability of the algorithm, and Levy flight is introduced int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…In this study, ten common test photos with varied histograms are subjected to HDAFAA comparison between the proposed methods for OTSU and Kapur's methods, as well as with recent benchmark optimization algorithms such as MTEMO, GA, PSO, and BF. Quantitative results show that HDAFA is highly efficient in terms of PSNR, mean, thresholds, iteration counts, and image segmentation quality [12]. Dongmei Wu and Chengzhi Yuan.…”
Section: Shikai Wang Et Al( 2021)mentioning
confidence: 99%
“…In this study, ten common test photos with varied histograms are subjected to HDAFAA comparison between the proposed methods for OTSU and Kapur's methods, as well as with recent benchmark optimization algorithms such as MTEMO, GA, PSO, and BF. Quantitative results show that HDAFA is highly efficient in terms of PSNR, mean, thresholds, iteration counts, and image segmentation quality [12]. Dongmei Wu and Chengzhi Yuan.…”
Section: Shikai Wang Et Al( 2021)mentioning
confidence: 99%
“…through the comparison of the above data, it can be found that each improved strategy has a certain degree of assistance to the improvement of the seeking performance of the algorithm, and the effectiveness of the different strategies is verified. The threshold selection criterion of the 2D maximum entropy (2D ME) algorithm is such that the total entropy of the segmented target and the background is maximized [22]. In the 2D segmentation method, not only each gray level information of the image is considered, but also the gray level information of its neighbors.…”
Section: Analysis Of the Effectiveness Of Improvement Strategiesmentioning
confidence: 99%
“…algorithm 25 and Threshold segmentation algorithm 26 are compared experimentally using the abnormal mammogram images. Table 8 shows the comparative analysis of various segmentation methods in terms of Se, Sp, and CSA.…”
Section: Sensitivity Sementioning
confidence: 99%